PERLINDUNGAN HUKUM BAGI TENAGA KERJA INDONESIA DI HONG KONG - Rizky Akbar Prabowo; Sutiarnoto Sutiarnoto; Jelly Leviza (Journal of USU International Law, 2014)
Abstract Indonesian Labor or communly called by workers is one of the biggest source of foreign exchange in Indonesia. In Asia, Indonesia is one of the largest countries in terms of contributing labor to other countries. In the placement until the deportations, should be existence of a rule of law that protects rather than the interests of the workers either own or of the recipient country. Legal norms that can be a rule in this case the norms of labor law and international law. The method used in this paper is a research library, which is by collecting materials from books, journals, internet, print media, international legal instruments and the results of other scientific papers are closely related to the intent and purpose of the preparation of this paper.   Keywords :      Indonesian Labor, Labor law, International law